EFFECTS OF POLY(2-ETHYL-2-OXAZOLINE) EXPOSURE ON OVARY HISTOLOGY OF ZEBRAFISH (Danio rerio) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2015)
Poly(2-oxazoline)s have been widely used in biomedical applications for the last years. They can mimick natural systems and they generally used as liposomes, drug and gene deliver and pseudopeptides. In this study histological effects of different doses (10 mg/L, 50mg/L) of poly(2-ethyl-2-oxazoline) on ovary tissue of zebrafish were investigated. After 5 days of administation, ovary tissues were dissected and histomorphological changes investigated under light microscope. Severe structural deformation in oocytes were monitored. Deterioration in germinal vesicle and openings at follicular epithelium, zona radiata and vitelline envelope were detected.
Keywords: poly(2-ethyl-2-oxazoline); zebrafish; ovary; histology; CYCLIC IMINO ETHERS; SWELLING BEHAVIOR; POLYMERIZATION